Structures of Naturally Evolved CUP1 Tandem Arrays in Yeast Indicate That These Arrays Are Generated by Unequal Nonhomologous Recombination - Zhao, Ying; Strope, Pooja K; Kozmin, Stanislav G; McCusker, John H; Dietrich, Fred S; Kokoska, Robert J; Petes, Thomas D (G3 : genes - genomes - genetics, 2014)
Abstract An important issue in genome evolution is the mechanism by which tandem duplications are generated from single-copy genes. In the yeast Saccharomyces cerevisiae, most strains contain tandemly duplicated copies of CUP1, a gene that encodes a copper-binding metallothionein. By screening 101 natural isolates of S. cerevisiae, we identified five different types of CUP1-containing repeats, as well as strains that only had one copy of CUP1. A comparison of the DNA sequences of these strains indicates that the CUP1 tandem arrays were generated by unequal nonhomologous recombination events from strains that had one CUP1 gene.